PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - VINA LUSIANA (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This research aims to increase students' motivation and learning outcomes by applying the Problem Based Learning. Where this model will create learning that is not rigid and full of cooperation between students, builds students' creative thinking in solving real problems given and trains students' readiness in understanding the material provided by the teacher. Problem Based Learning or problem-based learning is a teaching model characterized by real problems as a context for students to learn critical thinking and problem-solving skills and gain knowledge. This research was carried out in class X IPA3 of SMA Islam Nurul Fikri Boarding School Lembang and the time of the study followed the schedule for learning Mathematics with specialization in Science according to the class and schedule that researchers usually carried out when teaching at SMA Islam Nurul Fikri Boarding. The implementation of this classroom action research is carried out in 2 cycles, each cycle through four stages, namely, the planning stage, the implementation stage, the observation stage, and the reflection stage. After going through these stages, data related to the purpose of this study were obtained, namely to increase student motivation and learning outcomes. Based on the results of research on student learning motivation, information was obtained from questionnaire data on student learning motivation during the second cycle of action, it can be seen that student learning motivation increased from cycle I, where the comparison of the percentage results from the range of 20% to 49% to 80% to 100%, for the data on the average score of student learning motivation in the first cycle of 44 or about 55% increased to 68 or about 86% in the second cycle, the data on the average increase in student learning motivation during the implementation of the second cycle of action with the application of problem based learning was 31 %. Meanwhile, from student learning outcomes during the implementation of the cycle experienced a very significant increase from 47% to 83%. Thus it can be said that the application of Problem Based Learning can increase learning motivation and student learning outcomes. ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar siswa dengan penerapan model pembelajaran Problem Based Learning. Dimana model ini akan menciptakan pembelajaran yang tidak kaku dan penuh kerjasama antar siswa, membangun berpikir kreatif siswa dalam memecahkan masalah nyata yang diberikan serta melatih kesiapan siswa dalam memahami materi yang diberikan oleh guru. Problem Based Learning atau pembelajaran berbasis masalah adalah model pengajaran yang bercirikan adanya permasalahan nyata sebagai konteks untuk para peserta didik belajar berfikir kritis dan keterampilan memecahkan masalah serta memperoleh pengetahuan. Penelitian ini dilaksanakan dikelas X IPA3 SMA Islam Nurul Fikri Boarding School Lembang dan waktu penelitian mengikuti jadwal pembelajaran Matematika Peminatan IPA sesuai dengan kelas dan jadwal yang biasa peneliti laksanakan ketika mengajar di SMA Islam Nurul Fikri Boarding. Pelaksanaan penelitian tindakan kelas ini dilaksanakan dalam 2 siklus masing-masing siklus melalui empat tahapan yaitu, tahap perencanaan, tahap pelaksanaan, tahap observasi, dan tahap refleksi. Setelah melalui tahapan-tahapan tersebut maka diperoleh data-data yang berkaitan dengan tujuan penelitian ini yaitu untuk meningkatkan motivasi dan hasil belajar siswa. Berdasarkan hasil penelitian terhadap motivasi belajar siswa diperoleh informasi dari data angket motivasi belajar siswa saat dilakukannya tindakan siklus II dapat lihat bahwa motivasi belajar siswa meningkat dari siklus I, dimana perbandingan hasil persentasenya dari rentang 20% hingga 49% menjadi 80% hingga 100%, untuk data rata-rata skor motivasi belajar siswa di siklus I sebesar 44 atau sekitar 55% meningkat menjadi 68 atau sekitar 86% pada siklus II, data peningkatan rata-rata motivasi belajar siswa selama pelaksanaan tindakan siklus II dengan penerapan model pembelajaran problem based learning sebesar 31%. Sedangkan dari hasil belajar siswa selama pelaksanaan siklus mengalami peningkaran yang sangat signifikan dari 47% menjadi 83%. Dengan demikian dapat dikatakan bahwa penerapan Problem Based Learning dapat meningkatkan motivasi belajar dan hasil belajar siswa.